An Academic Review of the SIKE Attack in Post-Quantum Cryptography Failure - Naskar, Krishanu; Dey, Abhishek (International Journal of Computer Sciences and Engineering, 2025)
Supersingular Isogeny Key Encapsulation (SIKE) was a promising candidate in the National Institute of Standards and Technology (NIST) Post-Quantum Cryptography (PQC) standardization process, as it is distinguished by its exceptionally small key sizes, which makes it attractive for resource-constrained environments, and an elegant mathematical foundation rooted in supersingular elliptic curve isogenies. Its security based on the presumed hardness of computing isogenies between such curves. However, in August 2022, a groundbreaking attack by Castryck and Decru completely compromised SIKE, demonstrating its insecurity with practical polynomial-time complexity. This pivotal event led to SIKE`s immediate withdrawal from NIST`s standardization efforts, reshaping the evolving landscape of post-quantum cryptography and underscoring essential lessons in cryptographic design, evaluation, and diversity. A comprehensive academic analysis of the SIKE cryptographic scheme methodology and details of the specific nature of the Castryck-Decru attack that rendered it insecure is provided by this paper. It also discusses in brief the far-reaching implications for cryptographic design, standardization processes, and the pursuit of quantum-resistant algorithms, giving particular emphasis on the current state of post-quantum cryptography or PQC standardization as of 2025.